2013
DOI: 10.1016/j.bone.2012.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Localized deferoxamine injection augments vascularity and improves bony union in pathologic fracture healing after radiotherapy

Abstract: Background Medically based efforts and alternative treatment strategies to prevent or remediate the corrosive effects of radiotherapy on pathologic fracture healing have failed to produce clear and convincing evidence of success. Establishing an effective pharmacologic option to prevent or treat the development of non-unions in this setting could have immense therapeutic potential. Experimental studies have shown that Deferoxamine (DFO), an iron- chelating agent, bolsters vascularity and subsequently enhances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 24 publications
5
90
0
Order By: Relevance
“…Fig. 7 illustrates that angiogenesis is induced in endothelial cells through exposure to DFM which promotes capillarity in a 3D collagen based hydrogel (Matrigel) in a Ti-6Al-4V foam slice similar to previous observations of endothelial capillarity [20]. Fluorescent microscope images near the metal foam ligaments in the prepared slices, similar to Fig.…”
Section: Seeding Efficiency Cell Proliferation and Cell Adhesionsupporting
confidence: 83%
See 1 more Smart Citation
“…Fig. 7 illustrates that angiogenesis is induced in endothelial cells through exposure to DFM which promotes capillarity in a 3D collagen based hydrogel (Matrigel) in a Ti-6Al-4V foam slice similar to previous observations of endothelial capillarity [20]. Fluorescent microscope images near the metal foam ligaments in the prepared slices, similar to Fig.…”
Section: Seeding Efficiency Cell Proliferation and Cell Adhesionsupporting
confidence: 83%
“…Deferoxamine mesylate (DFM) (or deferoxamine (DFO)) promotes angiogenesis by inducing hypoxia [18,19], and it has been reported that endothelial cells are able to form capillaries in gel when exposed to DFM. A hypoxia mimetic environment has been reported to enhance bone repair and endothelial integrity restoration [20].…”
Section: Angiogenesis Induction In Matrix-infused Metal Foammentioning
confidence: 99%
“…Donneys et al (49) have recently shown that acute irradiation with low doses increases cellular movement and organization, whereas with high doses endothelial cells form fewer tubules in culture. In their study, time-lapse recording demonstrated a considerable increase in cellular organization, activity and locomotion in response to this low-dose therapy.…”
Section: Discussionmentioning
confidence: 98%
“…This dose was derived from an extensive literature search regarding the use of deferoxamine in long bone animal models, as well as our experimentation with this drug in recent years [18-21,26,27]. We implemented the injection of deferoxamine therapy during the active distraction period to coincide with the known augmentation of angiogenesis naturally occurring in response to the mechanical stretching of the callus [7,8,10].…”
Section: (12) Materials and Methodsmentioning
confidence: 99%